Determining Critical Success Factors of the Digital Transformation Using a Force-Directed Network Graph - Gianni Pasqual; Jürgen Jung; Bardo Fraunholz (Complex Systems Informatics and Modeling Quarterly)
Conducting a digital transformation is one of the major challenges for today’s companies as it is usually associated with a high risk. The reasons for this are manifold. Technologies are still evolving and there is no coherent standard for digital platforms enabling digitalization. Furthermore, it is not only about introducing new technology but also requires a fundamental change in an organization and its culture. Consequently, planning a digital transformation project (or program) requires a careful analysis of the company’s current situation and the envisioned objectives. This article investigates critical success factors for preparing and executing such a transformation. The success factors are identified by conducting a structured literature analysis. 13 scientific papers are identified and then analyzed quantitatively and qualitatively. The quantitative analysis is conducted by using force-directed network graphs. Both methods are then compared and discussed. The result shows that most critical success factors are related to the business change rather than to introducing technology. Leadership, strategy, vision, corporate culture, and customer centricity play a stronger role than a digital platform.